Quality profile of milk from high producing dairy cows vaccinated against mastitis - M. N. Isakova; U. V. Sivkova; M. V. Ryaposova; I. A. Shkuratova; A. V. Lysov (Ветеринария сегодня)
One of the raw milk quality criteria is the count of somatic cells, produced by the cow’s immune system to fight infectious diseases of the mammary gland. The paper presents the analysis of somatic cell count and total bacteria count of milk from cows, vaccinated against mastitis using Startvac vaccine. Tests were performed as a comparison between a dairy unit and a farm under different management conditions and using different milking techniques. Six months after the start of the vaccine application the somatic cell count at the dairy unit decreased by 60 thousand/ml, at the farm by 182 thousand/ml. The agent profile was represented by the following bacteria: Entеrococcus faecium, Staphylococcus aureus, Streptococcus spp., Pseudomonas aeruginosa. Staphylococcus saprophyticus, Staphylococcus epidermidis, Entеrococcus faecalis, Escherichia coli, Bacillus, Lactobacillus were also isolated from udder secretion. After a year of immunization somatic cell count both at the unit and on the farm decreased by 245 and 216 thousand/ml respectively; it is noteworthy that 43.75% of microflora isolated from mammary gland secretion was represented by Streptococcus spp. After two years of the vaccine use the somatic cell count was equal to 371 and 725 thousand/ml at the unit and on the farm respectively. Tests of mammary gland secretions revealed Streptococcus spp. in 27.27% of cases, Staphylococcus aureus and Entеrococcus faecium were isolated in 18.18% of tested samples. It was established that after three years of the vaccine use the major cause of mastitis in cows was Streptococcus spp. (55.00%). During four years of tests, a downward trend in somatic cell count of bulk milk from high producing dairy cows as well as in the number of agents responsible for inflammation in a mammary gland was detected. Somatic cell count of milk from vaccinated animals decreased by 286 and 432 thousand/ml at the unit and on the farm respectively. During the test period Staphylococcus aureus isolation rate declined by 19.41%.